Links between success in non-measurement and calculation tasks in area and volume measurement and pupils’ problems in this domain - Tůmová, Veronika; Vondrová, Naďa (Scientia in educatione, 2017)
Measurement in geometry belongs among key areas of school mathematics, however, pupils make serious mistakes when solving problems on measurement and hold misconception. The article focuses on possible links between lower secondary pupils’ (n = 870) success in solving non-measurement and in calculations tasks on area and volume and on their problems when solving measurement tasks. The study uses a mixed research design. Statistical methods are used to find correlations between the two types of tasks and a qualitative analysis is carried out to identify mistakes and misconceptions. The results show that there are indeed relatively strong links between success in non-measurement tasks and in calculation tasks and consequently when teaching this topic, attention must be paid to development of both types of skills. The study identified pupils’ mistakes in tasks which are within the Czech curriculum but which proved to be difficult for them, such as a missing link between an algebraic and geometric representations, a tendency to linearize and/or to employ pseudo-analytical thinking. The study identified differences between individual classes which point to the significant role of the teacher and/or influence of the textbook used.